1985
DOI: 10.1182/blood.v65.6.1318.bloodjournal6561318
|View full text |Cite
|
Sign up to set email alerts
|

Elevated adenosine deaminase and purine nucleoside phosphorylase activity in peripheral blood null lymphocytes from patients with acquired immune deficiency syndrome

Abstract: The purine metabolic enzymes adenosine deaminase (ADA) and purine nucleoside phosphorylase (PNP) are important in lymphocyte differentiation, and genetic deficiencies of either enzyme have been associated with hereditary immunodeficiency states. Both ADA and PNP activity were measured in null cell-enriched and T cell-enriched peripheral blood lymphocytes from 16 patients with the acquired immune deficiency syndrome (AIDS), seven patients with the AIDS-related symptom complex (ARC), and seven asymptomatic homos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Indeed, the inhibition of ADA binding to CD26 by viral particles is likely to occur in vivo , as it has been shown that the 50% inhibitory concentration (IC 50 ) for inhibition of ADA binding to the Jurkat T‐cell line is similar to the dissociation constant ( K d or affinity) values reported for binding of gp120 to CD4 43,67 . However, ADA is found at high levels in the serum of HIV‐infected patients, 68–73 and this could be, at least in part, attributable to the displacement of ADA from its anchor on the T‐cell surface. As previously reported, a CD4–gp120 interaction is required for efficient inhibition of ADA binding to CD26 44 …”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the inhibition of ADA binding to CD26 by viral particles is likely to occur in vivo , as it has been shown that the 50% inhibitory concentration (IC 50 ) for inhibition of ADA binding to the Jurkat T‐cell line is similar to the dissociation constant ( K d or affinity) values reported for binding of gp120 to CD4 43,67 . However, ADA is found at high levels in the serum of HIV‐infected patients, 68–73 and this could be, at least in part, attributable to the displacement of ADA from its anchor on the T‐cell surface. As previously reported, a CD4–gp120 interaction is required for efficient inhibition of ADA binding to CD26 44 …”
Section: Discussionmentioning
confidence: 94%
“…Functional, morphologic and structural differences in mononuclear cells, including the T/B/NK subsets and monocytes, in healthy subjects and HIV+/AIDS patients have been consistently reported for some time [23,25,27]. But the cytoplasmic metabolic processes [1] in immunocompetent PBM cells have received less detailed investigation, apart from the purine and pyrimidine enzymatic and metabolic pathways [33,34,44], and most of these studies have concerned the cell surface, mitochondria and nuclear organelles [13,24,32,38]. The antioxidant status and redox related pathways have recently received increased attention, since it has been suggested that oxidative stress could be implicated in several aspects of the pathogenesis of HIV disease, including viral replication, inflammatory response, decreased immune cell proliferation, loss of immune function and apoptotic cell death [35].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Moreover, ADA binding to CD26 is inhibited by HIV-1 envelope glycoprotein gp120, resulting in impaired ADA co-stimulation in cells of HIV-infected individuals. 32,33 Although it remains unclear whether high levels of ADA accumulate in the serum of HIV-infected patients when gp120 disrupts the interaction between ADA-CD26, [34][35][36][37][38] gp120 can reduce both the ADA-induced secretion of cytokines and ADA-enhanced T-cell proliferation in HIV-infected individuals. 32 Importantly, the effect of ADA in cells from HIV-infected patients is positively correlated with the percentage of CD4 + cells and nadir CD4 counts, and it is negatively correlated with viral load.…”
Section: Ada and Hiv-1 Infectionmentioning
confidence: 99%